2007
DOI: 10.1016/j.pestbp.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histological hepatic changes of Nile tilapia Oreochromis niloticus exposed to carbaryl

Abstract: The purpose of this study was to evaluate biochemical and morphological responses induced by carbaryl in the liver of Nile tilapia (Oreochromis niloticus) exposed during 21 days to sublethal concentrations (0.25 and 0.5 mg L À1 ), testing also recover for 14 days in clean water, after 14 days exposure. The activities of the following enzymes were measured: superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST), glutathione reductase (GR), and reduced (GSH) and oxidized glutathione (GSSG). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 46 publications
7
32
0
1
Order By: Relevance
“…In Fig. 8 Liver section (H&E, ×40) of L. rohita fingerlings from a group that was: a control (unexposed) and fed with control diet with normal hepatic tissue structure; b exposed to endosulfan and fed with control diet showing extensive vacuolation and marked disruption of cordal arrangements of hepatocytes; c exposed to endosulfan and fed with betaine diet showing mild disarray of hepatic cords and moderate vacuolation; d exposed to endosulfan and fed with lecithin diet showing mild disarray of hepatic cords and moderate vacuolation studies by Matos et al (2007) on carbaryl (an organochlorine pesticide) at sublethal toxicity, compared to control, liver SOD activity was decreased up to the 14th day but increased on 21st day while catalase remained significantly decreased from days 7 through 21. Studies involving propiconazole (Li et al 2010) found significantly increased activity of catalase in treated fish at the 7th day but decreased at the 20th day, and SOD was likewise decreased at the 20th day.…”
Section: Discussionmentioning
confidence: 99%
“…In Fig. 8 Liver section (H&E, ×40) of L. rohita fingerlings from a group that was: a control (unexposed) and fed with control diet with normal hepatic tissue structure; b exposed to endosulfan and fed with control diet showing extensive vacuolation and marked disruption of cordal arrangements of hepatocytes; c exposed to endosulfan and fed with betaine diet showing mild disarray of hepatic cords and moderate vacuolation; d exposed to endosulfan and fed with lecithin diet showing mild disarray of hepatic cords and moderate vacuolation studies by Matos et al (2007) on carbaryl (an organochlorine pesticide) at sublethal toxicity, compared to control, liver SOD activity was decreased up to the 14th day but increased on 21st day while catalase remained significantly decreased from days 7 through 21. Studies involving propiconazole (Li et al 2010) found significantly increased activity of catalase in treated fish at the 7th day but decreased at the 20th day, and SOD was likewise decreased at the 20th day.…”
Section: Discussionmentioning
confidence: 99%
“…Dramatical changes in the physical behaviour of fish B. gonionotus were recorded in treated profenofos specimens. Histological changes associated with pesticides in fish have been studied by many authors (Wester and Canton, 1991;Bhuiyan et al, 2001;Gernhofer et al, 2001;Thophon et al, 2003;Velmurugan et al, 2007;Matos et al, 2007;Ogueji et al, 2013;Nannu et al, 2015;Mostakim et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Matos et al (2007) reported that hyperglycemic was indication of a disruption in carbohydrate metabolism, possibly due to enhanced glucose 6-phosphatase activity in liver, elevated breakdown of liver glycogen, or the synthesis of glucose from extrahepatic tissue proteins and amino acids. Glucose level might elevate to cope with the increased energy demand during pesticide-induced which is important pathway for the recovery from stress (Özgür et al, 2011).…”
Section: Blood Biochemical Parametersmentioning
confidence: 99%